Futurologi Pendidikan Bahasa di Era Digital: Eksplorasi AI untuk Literasi Anak Usia SD - Tyasmiarni Citrawati; Teguh Supriyanto; Tri Suminar; Haryadi Haryadi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The development of digital technology has revolutionized the paradigm of elementary school education. Artificial Intelligence (AI) has become one of the significant breakthroughs in the application of artificial intelligence in the learning process. The purpose of this study is to explore the integration of AI in language learning to improve the digital literacy of elementary school children in the context of educational futurology. Through a literature study and trend analysis approach to identify various forms of AI utilization, such as educational chatbots, NLP (Natural Language Processing)-based applications, and adaptive platforms tailored to children's learning styles. This study discusses the ethical, pedagogical, and cultural challenges in the application of AI, as well as its implications for the development of language skills, children's understanding of literature, and the strengthening of cultural identity. The results of the analysis show that AI has great potential in supporting comprehensive digital literacy, provided that it is designed with a humanistic and contextual approach. The limitations of this study lie in the exploratory and predictive nature of the analysis, the limitations of generalization due to the heterogeneity of AI interventions, and the potential for publication bias that needs to be taken into account. Further long-term empirical research is needed to validate these findings. The practical implications of this research are the importance of synergy between educators, technology developers, and policymakers. Teachers are trained to become active users, technology developers design integrated contextual content, and policymakers develop ethical guidelines and adaptive regulations for inclusive, sustainable, and culturally sensitive AI implementation